Toward a Maqāṣid-Based Legal Reform: Systemic Thinking for Social Transformation in the Modern Muslim World - Uthman Mehdad Al-Turabi; Jasser Auda (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2025)
This article re-examines the role of maqāṣid al-sharī‘ah in contemporary Islamic legal reform, emphasising the need to move beyond classical textualism towards a purposeful paradigm of law grounded in human welfare and moral intentionality. Through a systems-theoretical approach, the study seeks to reconstruct Islamic jurisprudence as a dynamic framework capable of responding to modern challenges such as human rights, human dignity, social justice, and environmental sustainability. The theoretical framework builds upon six systemic features—connectivity, wholeness, openness, interrelated hierarchy, multidimensionality, and purposiveness—which serve as analytical criteria for evaluating how Islamic law can function both ethically and adaptively. Using a normative-qualitative approach, the study compares three reform contexts: family law reform in Indonesia, the constitutional embedding of maqāṣid in Morocco, and penal reform in post-revolution Tunisia. Data are drawn from legislative texts, constitutional provisions, and public policy documents, which are then mapped through the systemic maqāṣid framework. The results show that reforms based on systemic maqāṣid reasoning lead to not only procedural but also transformative legal change, which supports both divine intent and human dignity. The novelty of this research lies in operationalising maqāṣid as a meta-legal philosophy that bridges normative principles with institutional practice. By situating maqāṣid within the discourse of governance and public policy, this article affirms the relevance of Islamic law as a living ethical system—one that is just, humane, and capable of sustaining moral transformation in the modern Muslim world.